2017
DOI: 10.1007/s11011-017-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurogenesis in the C57BL/6J mice at early adulthood following prenatal alcohol exposure

Abstract: We examined the effect of chronic prenatal alcohol exposure (PAE) on the process of adult neurogenesis in C57BL/6J mice at early adulthood (PND 56). Pregnant mice, and their in utero litters, were exposed to alcohol, through oral gavage, on gestational days 7-16, with recorded blood alcohol concentrations averaging 184 mg/dL (CA group). Two control groups, sucrose (CAc) and non-treated (NTc) control groups were also examined. The brains of pups at PND 56 from each experimental group were sectioned in a sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…All of these findings indicate that a single dose of perinatal ethanol diminishes the progenitor cells and thus reduces adult neurogenesis (Ieraci and Herrera, 2007). Pregnant mice administrated with alcohol for 10 days, starting from gestational day 7, produced a reduction in DCX-positive cells but not Ki-67-positive cells in offspring prenatally exposed to alcohol when analyzed at postnatal day 56, suggesting that prenatal alcohol exposure maintains the damage throughout the adolescent and adult lifespan (Olateju et al, 2018). This observation is also perceived in other species, as macaques prenatally exposed to alcohol showed decreased neurogenesis in the young adult stage (Fedorchak and Miller, 2019).…”
Section: Hippocampal Effects Of Alcohol In Prenatal and Neonatal Devementioning
confidence: 88%
“…All of these findings indicate that a single dose of perinatal ethanol diminishes the progenitor cells and thus reduces adult neurogenesis (Ieraci and Herrera, 2007). Pregnant mice administrated with alcohol for 10 days, starting from gestational day 7, produced a reduction in DCX-positive cells but not Ki-67-positive cells in offspring prenatally exposed to alcohol when analyzed at postnatal day 56, suggesting that prenatal alcohol exposure maintains the damage throughout the adolescent and adult lifespan (Olateju et al, 2018). This observation is also perceived in other species, as macaques prenatally exposed to alcohol showed decreased neurogenesis in the young adult stage (Fedorchak and Miller, 2019).…”
Section: Hippocampal Effects Of Alcohol In Prenatal and Neonatal Devementioning
confidence: 88%
“…Quantification of immature neurons labeled with DCX in mouse was lower in the group of individuals exposed to alcohol in the prenatal period compared to controls. Moreover, DCX levels were lower in males than in females ( 108 ). Broadwater et al obtained similar results after PAE by oral gavage on PND28–48, with decreased DCX levels in the DG of adolescent mice.…”
Section: Developmental Stages Of the Fetal Brainmentioning
confidence: 95%
“…Thus, DCX‐positive cells represent a set cells across a broad developmental spectrum, ranging from immature neural progenitor (INP) cells (also known as type 2B cells) to immature granule neurons (IGN) (Kronenberg et al, 2003). Four papers assessed DCX immunoreactivity in the dentate gyrus (Table 2) following perinatal EtOH exposure (Elibol‐Can et al, 2014; Gil‐Mohapel et al, 2011, 2014; Olateju et al, 2018). Two papers showed no change in DCX immunoreactivity (Elibol‐Can et al, 2014; Gil‐Mohapel et al, 2014), one showed a significant decrease in DCX‐positive cells that was restricted to females (Gil‐Mohapel et al, 2011), and one paper found a decrease in DCX cells in both males and females (Olateju et al, 2018) (see Fig.…”
Section: Resultsmentioning
confidence: 99%